Maternal and perinatal outcomes of uterine rupture in Lubumbashi, Democratic Republic of Congo - Kitenge, Jacques Ngoy; Mukuku, Olivier; Kinenkinda, Xavier K; Kakudji, Prosper L (Clinical Journal of Obstetrics and Gynecology, 2020)
Introduction: Uterine rupture is one of the peripartum complications, which cause nearly about one out of thirteen maternal deaths. This study aimed to assess the prevalence and associated factors of mortality among women with uterine rupture in referral hospitals of Lubumbashi, in the south east part of the Democratic Republic of Congo. Methods: Institution based cross sectional study was conducted from December 1st, 2012 to 31st, 2016 on uterine rupture. During the study selected 158 women were included by using exhaustive sampling method. Data were checked, coded and analyzed into STATA version 12. Chi-square test was used to identify the predictors of maternal and perinatal mortalities in women with uterine rupture and 95% Confidence Interval of odds ratio at p - value less than 0.05 was taken as a significance level. Results: The overall prevalence of uterine rupture was 0.49%. The average age of the patients was 29.5 ± 6.2 years and 71.52% of them were between 20 and 34 years old; more than 60% had a parity ≥4 (average parity: 4.7 ± 2.5). 81.17% of the cases had a fully ruptured uterus and 51.17% of the uterine ruptures were located in the lower segment. Repair of the pregnant ruptured uterus was performed in 93.04% of the cases and hysterectomy in 5.06%. Maternal and perinatal mortalities were 8.86% and 72.04% respectively. Regarding maternal mortality, no parameter showed a significant association with maternal death. As for perinatal mortality, parity ≥4, complete rupture and segmento-corporeal lesion were significantly associated with perinatal death (p < 0.05). Conclusion: Uterine rupture remains one of the causes of maternal and perinatal mortality in Lubumbashi. The place occupied by uterine ruptures in obstetric activity requires joint and urgent action by all stakeholders in the health system in order to combat this scourge, witness to poor quality obstetric care.